ST-Depresi pada Infark Miokard Akut dengan Elevasi Segmen ST–Pentingnya Perubahan Resiprokal pada Elevasi Segmen ST yang Minimal - Myrtha, Risalina; Wijayanto, Matthew Aldo; Putri, Desy Puspa; Hermawati, Berty Denny (Fakultas Kedokteran Universitas Trisakti, 2024)
Coronary artery disease remains the leading cause of mortality globally. Management of ST-elevation myocardial infarction (STEMI) starts from the point of first medical contact. Time delay to treatment influences the mortality in STEMI patients. The aim of this study is to underline the importance of reciprocal ECG changes in helping diagnosis STEMI with subtle ST elevation. We present an obese and hypertensive male patient with atypical symptoms of MI and was diagnosed as peptic ulcer. The ECG showed subtle ST elevation in inferior ECG leads and reciprocal changes in I and aVL. Highly sensitive troponin was elevated. Serial ECG showed evolution, thus revealed acute inferior MI. Successful percutaneous coronary intervention was performed. ECG is one of the most important diagnosis tools in STEMI and a cornerstone to direct the decision to immediate reperfusion therapy. Minimal ST-elevation often leads to inappropriate diagnosis, thus delayed the time to reperfusion. A study shows that 11-23% of STEMI do not reach the cutoff for accepted ECG criteria. In a study of infarctions with minimal ST-elevation, reciprocal changes are reported in 58% of all cases. Reciprocal ECG changes is extremely useful to help identifying STEMI in the absence of obvious ST-elevation on ECG